ASSESSING THE QUALITY OF TOURISM SERVICES AT MERANGIN GEOPARK, JAMBI THROUGH SENTIMENT ANALYSIS - Asrinaldi; Verinita; Mailinar; Nursyirwan Effendi (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to investigate the correlation between customer satisfaction and positive feedback posted on Google Maps, along with visitors' perceptions of the Geopark service. Geopark, a form of tourist destination highlighting natural beauty, environment, and sustainability, places significant emphasis on sustainable development principles to ensure its environmentally responsible and economically beneficial impact on local communities. Service satisfaction stands as a pivotal element in upholding Geopark tourism's success. Numerous researches have indicated that visitor contentment is intertwined with service quality, information provision, facilities, and pricing. Employing sentiment analysis techniques on Google Maps comments, the study unveiled that a majority of visitors expressed satisfaction with the Geopark service. Within the sentiment analysis of favorable comments on Google Maps, the agreement level displayed a moderate range of 0.41-0.60. This signifies that the Geopark service partially met visitors' requirements and offered a somewhat positive encounter. Certain visitors also contributed insights and recommendations for elevating service excellence and enriching the tourism venture. Nonetheless, alongside positive remarks, visitor sentiments exhibited variations concerning the Geopark service. To conclude, service satisfaction and the advancement of an environmentally conscious and sustainable Geopark tourism model in Merangin Jambi are pivotal for ensuring the sector's triumph. Positive comments on Google Maps can drive the continuous enhancement of service standards; however, it is equally crucial to consider visitors' diverse sentiments to rectify deficiencies and provide an enhanced tourism experience.